2019
DOI: 10.36632/mejas/2019.9.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficiency and Response of Quinoa Plant to Nitrogen Fertilization levels

Abstract: A field experiment was conducted to evaluate the response of the quinoa yield to nitrogen (N) fertilization, the nitrogen use efficiency (NUE) as well as the correlation coefficient to determine the important traits that contribute in determining the productivity of quinoa crop. Three levels of N fertilizer (i.e., 0, 80 and 160 kg N ha-1) were used and laid out in a randomized complete block design with four replicates. The results showed that all tested characteristics were significantly increased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
8
7
0
Order By: Relevance
“…Similar YLD was observed by Almadini et al. (2019) in cultivar Chipaya under well‐nitrogen field condition (18.08 g/plant) in Saudi Arabia. A key target trait for improvement in quinoa is PLH because tall plants tend to lodge.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar YLD was observed by Almadini et al. (2019) in cultivar Chipaya under well‐nitrogen field condition (18.08 g/plant) in Saudi Arabia. A key target trait for improvement in quinoa is PLH because tall plants tend to lodge.…”
Section: Discussionsupporting
confidence: 87%
“…In Egypt, the cultivar Danish KVL3704 had a grain yield of 12.7-17.2 g/plant (Nagib et al, 2020) under field conditions. Similar YLD was observed by Almadini et al (2019) in cultivar Chipaya under well-nitrogen field condition (18.08 g/plant) in Saudi Arabia. A key target trait for improvement in quinoa is PLH because tall plants tend to lodge.…”
Section: Discussionsupporting
confidence: 82%
“…The protein content of N0P0K0 was 11.35%, then it increased to 13.55% at the fertilizer level N30 -P25 -K20, then it increased to 20.75% at the fertilizer level N180 -P150 -K120. [30] also mentioned that nitrogen fertilizer treatments (80, 160 kg nitrogen h -1 ) caused significant differences in the values of total protein content in the dry grain of quinoa plant, as the protein values were 14.81%, 15.63% and 17.13%. Respectively, while there were no significant differences between the comparison treatment and (80,160) kg Nh -1 , this means that the protein content in the dry grain flour of the quinoa plant increases with the increase in the application rates of nitrogen fertilizer.…”
Section: Percentage Of Protein In Quinoamentioning
confidence: 99%
“…Quinoa is also resistant to adverse environmental conditions such as temperature from -5 to 37 o C, one of the best salt and drought tolerant crops [1]. However, for quinoa to grow well and produce high yield of seed with good nutritional quality, proper fertilization is required [2][3][4]. The literature also showed that the planting density is an important factor deciding the yield and quality of quinoa in addition to other aspects like the difference in variety, fertilizing procedures and growing seasons [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, for quinoa to grow well and produce high yield of seed with good nutritional quality, proper fertilization is required [2][3][4]. The literature also showed that the planting density is an important factor deciding the yield and quality of quinoa in addition to other aspects like the difference in variety, fertilizing procedures and growing seasons [3,5,6]. Vietnam is one of the most severely impacted countries of droughts caused by climate changes [7] so the selection and implementation of a strong tolerant crop are very necessary for further development of the agriculture.…”
Section: Introductionmentioning
confidence: 99%